Analysis Of Factors Influencing Consumer Interest In Purchasing Napoleon Cake As A Typical Medan Souvenir - Zuliyansah Zuliyansah; Anggia Ramadhan; Rahmad Sembiring (Universitas Dehasen Bengkulu, 2026)
This study aims to examine the effect of product quality, price, and service on consumers’ purchase intention of Napoleon cake as a typical souvenir from Medan. The research adopts a quantitative approach with data analyzed using multiple linear regression analysis. The sampling technique employed was non-probability sampling, involving 100 respondents. The findings reveal that product quality has a positive and significant influence on consumers’ purchase intention. Similarly, price and service both show positive and significant effects on consumers’ purchase intention. Simultaneously, product quality, price, and service collectively have a positive and significant impact on consumers’ purchase intention toward Medan Napoleon cake. R Square value of 0.197 (19.7%) indicates that the variation in purchase intention can be explained by these three variables, while the remaining 80.3% is influenced by other factors not included in this study.